2022
DOI: 10.1088/1742-6596/2243/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

The Study of the Swelling Degree of the PVA Hydrogel with varying concentrations of PVA

Abstract: Hydrogel is composed of a three-dimensional network of hydrophilic polymers and can swell when placed in an aqueous media. Polyvinyl alcohol (PVA) is a common polymer used to produce hydrogels because it has biocompatibility, non-toxicity, chemical stability, low cost, and excellent mechanical strength. In this study, the PVA solutions were prepared with concentrations of 6%, 8%, 10%, and 12% in distilled water. The precursor solutions underwent a freeze-thaw cycle with a freezing temperature of -25 °C for 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…The root-mean-square deviation (RMSD) was employed to determine whether the system had reached equilibrium, and then the equilibrium state was corroborated by observing the changes in end-to-end distance and radius of gyration over time, as shown in Figure S1. For our model, the system density was calculated with the experimental water gel density, as shown in Figure S2, and the result was consistent with the experimental value of 1 g/cm 3 . , This comparison demonstrates the credibility of our simulation approach in describing the spatial structure and intermolecular interactions within the system.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The root-mean-square deviation (RMSD) was employed to determine whether the system had reached equilibrium, and then the equilibrium state was corroborated by observing the changes in end-to-end distance and radius of gyration over time, as shown in Figure S1. For our model, the system density was calculated with the experimental water gel density, as shown in Figure S2, and the result was consistent with the experimental value of 1 g/cm 3 . , This comparison demonstrates the credibility of our simulation approach in describing the spatial structure and intermolecular interactions within the system.…”
Section: Resultssupporting
confidence: 75%
“…For our model, the system density was calculated with the experimental water gel density, as shown in Figure S2, and the result was consistent with the experimental value of 1 g/cm 3 . 56,57 This comparison demonstrates the credibility of our simulation approach in describing the spatial structure and intermolecular interactions within the system. By using two different methods to measure chitosan-phenol and DB-PEO, viz.…”
Section: Effects Of the Degree Of Phenol Substitution On Chitosan-phe...mentioning
confidence: 60%
“…Previous studies have shown the effect of variations in solution concentration of the polymer on hydrogel properties. Syifa et al found that with decreasing PVA concentration, the resulting hydrogel became softer but the swelling value increased [80]. Research by Waresindo and Edikresnha showed the same conclusion when loading PVA hydrogel with guava leaf extract and red betel extract [79,81].…”
Section: Solution Concentrationmentioning
confidence: 82%
“…The concentration of a polymer solution is expressed as the weight ratio of the polymer to the solvent. Decreasing the polymer concentration in the solution will decrease the viscosity of the solution and reduce the cross-linking density of the hydrogel, which results in a softer gel [79,80]. Previous studies have shown the effect of variations in solution concentration of the polymer on hydrogel properties.…”
Section: Solution Concentrationmentioning
confidence: 99%
“…On the other hand, synthetic polymers generally have strong mechanical properties but usually poor biological activity . An example of synthetic polymers that have been used to synthesize hydrogels is poly­(vinyl alcohol) (PVA) . PVA is soluble in water, and it can be used to form a hydrogel by means of the freeze–thaw technique .…”
Section: Introductionmentioning
confidence: 99%